Design of wood columns under real fire action - Haksever, Ataman; Savaş, Sedat (My University, 2005)
The main objective of this study is to develop an analytical model for determination of charring wood as well as deformation state of timber structures exposed to fire. In this study, the ideas of previous Works have been further developed and improved. This study also includes well defined experiments. In these experiments, fundamental variables such as the hot gas temperature, temperature development in cross-section rate of charring have been recorded. This relatively complete experimental setup enables verification of the analytical model to be carried out. By this, discussion of developed model in conjunction with comparison of the numerical result with the measured relationships are made, which resulted in finally preparation of the design charts of wood columns under real fire action. A good agreement is observed between the experimental and the calculated results.
Gerçek Yangin Etkisi Altinda Ahşap Kolonlarin Dizayni
Keywords: Charring rate; Fire engineering; Flash over; Real fire; Wood columns